On the Wildfire Propagation in Flat Lands - Dehkordi, H. R. (Trends in Computational and Applied Mathematics, 2023)
Due to global warming, wildfires became more severe and frequent than in the past, and more complex mathematics is needed to provide the model of propagation and predict the behavior of the fire. In this work, for a wildfire spreading in some flat land of zero slope, by using Randers metric the equations of wavefronts and wave rays are provided which lead to presenting a more precise and reliable model of propagation. By considering some hypothetical fire in Boa Nova National Park as an example, a simulation is implemented.